Relationship between periodontal disease and cognitive decline: a literature review (Brazilian Journal of Health Research, 2025)
Introduction: Periodontal disease, or periodontitis, is a chronic infection involving gram-negative microorganisms that can produce both local and systemic changes; in its severe forms, it affects more than 1 billion people worldwide. Cognition is the set of mental capacities comprised of various functions, assisting the individual in making decisions and maintaining their autonomy. There are no specific treatments that can prevent or delay the progression to dementia syndromes; however, there are reversible causes of cognitive decline, such as psychiatric, metabolic, endocrinological, hematological, drug-related, and infectious causes. Objectives: To analyze the association between periodontal disease and cognitive decline through a literature review. Methods: A comprehensive electronic search was conducted across MEDLINE (Medical Literature Analysis and Retrieval System Online), Web of Science, and Scopus, with a search period between 2013 and 2024. Results: Periodontopathogenic bacteria, such as P. gingivalis, T. forsythia, and T. denticola, can reach distant tissues, including the brain, and are associated with cognitive decline and dementia. Animal studies have shown that P. gingivalis can cause neuronal damage. Studies suggest a possible association between periodontitis and cognitive decline, with periodontal inflammation potentially contributing to neuroinflammation. Although evidence points to a correlation between periodontal pathogens and inflammatory markers in the brain, a direct causal relationship has not yet been confirmed. Conclusions: There is insufficient evidence to establish a causal association between these two pathologies. Therefore, further studies are needed to determine whether periodontal disease can induce or exacerbate the neuroinflammation that leads to cognitive decline. More experimental and longitudinal research is needed to understand the mechanisms involved and confirm this connection.
Keywords: Cognitive Dysfunction; Periodontal Diseases; Periodontitis